Environment evolution and values : Studies in Man, Society and Science - Chattopadhyaya, D.P. (New Delhi)
This book is mainly concerned with environment evolution and values, -- terms which figure in its very title. The basic underlying concepts of evolution are natural environment highlighted by Lamarck (1744-1829), Heredity and natural selection emphasized by Darwin (1809-1882) and genetic mutation first developed by Mendel (1822-1884). Though these three great life scientists brought to light three main components of biological evolution, these were known and formulated by others for a long time. Nature is ordinarily believed to be a world of facts governed by law of causality and values are said to be rooted in human freedom. The author of this book has paid special attention to the so-called value-fact dualism with special reference to changing theories of evolution, and an attempt has been made to show that the supposed dualism is untenable. This book will be of interest to philosophers, life scientists and social scientists. It will be of interest also to the general readers.
Keywords: Human ecology